2022
DOI: 10.3346/jkms.2022.37.e204
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of MPO-ANCA-Associated Vasculitis Following Heterologous mRNA1273 COVID-19 Booster Vaccination

Abstract: Despite that clinical trials have been examining the safety profile of coronavirus disease 2019 (COVID-19) vaccines, there are concerns about long-term side effects as the number of vaccinations increases. Herein, we report a case of new-onset renal-limited anti-myeloperoxidase (MPO) antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis after booster vaccination with the mRNA 1273 (Moderna) vaccine. A 72-year-old woman with no specific past history, and who had a normal renal function, developed ANC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Based on renal biopsy results, ANCA-associated pauci-immune crescentic glomerulonephritis was diagnosed. After high-dose steroid treatment and plasmapheresis, the patient’s symptoms and renal function improved [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on renal biopsy results, ANCA-associated pauci-immune crescentic glomerulonephritis was diagnosed. After high-dose steroid treatment and plasmapheresis, the patient’s symptoms and renal function improved [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…AAV is classified into three types based on clinical features, namely granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA), and eosinophilic GPA (EGPA) [ 111 ]. A total of 17 new-onset AAV cases have been reported, including 5 cases of PR3-ANCA vasculitis, 9 cases of MPO-ANCA vasculitis, and 3 cases of dual-positive MPO- and PR3-ANCA vasculitis [ [112] , [113] , [114] , [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] , [123] , [124] , [125] , [126] , [127] , [128] ]. The majority of cases were women (11/17, 64.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Tese fndings are consistent with existing reports. Tere is also a report of ANCA-associated [18]. A recent comparative study on using the same vaccine as the primary series (homologous boosters) versus using a diferent vaccine (heterologous boosters) showed that the immunogenicity of heterologous boosting was generally similar to or greater than those of homogenous boosting [19].…”
Section: Discussionmentioning
confidence: 99%
“…The data provided in the present study demonstrate that RBD-specific antibody induction suppresses NET formation, supporting the preventive effects of vaccination in the case of vascular complications. Unfortunately, a number of case reports demonstrate that neutrophil-associated complications and vasculitis can be triggered by vaccination [ 45 , 46 ]. Enhanced pathogen-induced neutrophil recruitment in the case of RBD-specific antibody induction observed in the present study can in part explain the adverse reactions to vaccination.…”
Section: Discussionmentioning
confidence: 99%